Third Five Year Plan (1961-1966) Volume II Government of Bhopal - Planning Commission (Planning Commission, 1961)
Minor irrigation.—Only an area of 20.3S lakh acres had irrigation facilities when the second plan was started. During the second plan period an additional irrigation potential of 4.27 lakh acres was created, of which 3.43 lakh acres was through minor irrigation schemes. The total irrigation potential, thus, created by the end of the second plan was of the order of 24.65 lakh acres which is only 5.8 per cent of the total area of 415.46 lakh acres under cultivation in the State. A total provision of Rs. 7.00 crores has been made under agriculture sector for advancing loans for wells, pumping sets, persian wheels, etc. It is expected that an additional irrigation potential of 2.38 lakh acres would be created in the third plan through this programme.
Government of Bhopal